People, Places and Policy : Knowing Contemporary Wales Through New Localities. - Jones, Martin. (Regions and Cities Series, 2015)
This consolidation of Wales as a regional/national space of social and economic governance, with increasingly sharp territorial definition has refocused attention on the dynamics of spatial difference within the country. The authors of the book analyse the impact of the changes and the way the Welsh localities stack up against one another, with important conclusions for the economy, policy and governance.